Insufficiencies in sensory systems reweighting is associated with walking impairment severity in chronic stroke: an observational cohort study - Awosika, Oluwole O.; Garver, Amanda; Drury, Colin; Sucharew, Heidi J.; Boyne, Pierce; Schwab, Sarah M.; Wasik, Emily; Earnest, Melinda; Dunning, Kari; Bhattacharya, Amit; Khatri, Pooja; Kissela, Brett M. (Frontiers in Neurology, 2023)
Background: Walking and balance impairment are common sequelae of stroke and significantly impact functional independence, morbidity, and mortality. Adequate postural stability is needed for walking, which requires sufficient integration of sensory information between the visual, somatosensory, and vestibular centers. "Sensory reweighting" describes the normal physiologic response needed to maintain postural stability in the absence of sufficient visual or somatosensory information and is believed to play a critical role in preserving postural stability after stroke. However, the extent to which sensory reweighting successfully maintains postural stability in the chronic stages of stroke and its potential impact on walking function remains understudied. Methods: In this cross-sectional study, fifty-eight community-dwelling ambulatory chronic stroke survivors underwent baseline postural stability testing during quiet stance using the modified Clinical test of Sensory Interaction in Balance (mCTSIB) and assessment of spatiotemporal gait parameters. Results: Seventy-six percent (45/58) of participants showed sufficient sensory reweighting with visual and somatosensory deprivation for maintaining postural stability, albeit with greater postural sway velocity indices than normative data. In contrast, survivors with insufficient reweighting demonstrated markedly slower overground walking speeds, greater spatiotemporal asymmetry, and limited acceleration potential. Conclusions: Adequate sensory system reweighting is essential for chronic stroke survivors' postural stability and walking independence. Greater emphasis should be placed on rehabilitation strategies incorporating multisensory system integration testing and strengthening as part of walking rehabilitation protocols. Given its potential impact on outcomes, walking rehabilitation trials may benefit from incorporating formal postural stability testing in design and group stratification.